Citation for the BAOMS Surgery Prize 1998 - P.J. LEOPARD (Blackwell Synergy, 2000)
Mark McGurk was born in 1953, the year before I left school. He was brought up in Africa and was apparently remarkably camera-shy. He lived what passes for a normal life in the wilds and developed passions for fishing and playing rugby which have remained lifelong interests.